Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan Terhadap Disiplin Kerja di Mediasi oleh Kepuasan Kerja pada Karyawan PT MEA - Tri Mulyani Kartini; Etty Zuliawati Zed (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
In the era of disruption and global competition, employee work discipline has become a crucial factor influencing the operational effectiveness and efficiency of companies. This study aims to analyze the effect of work environment and leadership style on work discipline, with job satisfaction as a mediating variable, among employees of PT MEA, an automotive component manufacturing company in Cikarang. A quantitative approach was employed using a survey method with a saturated sample of 70 production division employees. Data were collected through questionnaires and analyzed using SmartPLS 3.2.9 to examine validity, reliability, as well as the direct and mediating effects among variables. The results indicate that the work environment has a significant effect on both work discipline and job satisfaction, while leadership does not have a significant effect on either variable. Moreover, job satisfaction was not found to mediate the relationship between work environment or leadership and work discipline. These findings suggest that the work environment is a more dominant factor than leadership and job satisfaction in improving employee discipline. This study provides practical implications for human resource management to focus on improving the work environment to enhance employee discipline and productivity.